IMPLEMENTASI PEMBELAJARAN DOUBLE TRACK DI SMAN 4 SIDOARJO UNTUK MENINGKATKAN KESIAPAN BERWIRAUSAHA - Evawati, Diana; Susilowati, Susilowati; Misbahudin, Agus Ridwan (Steam Engineering, 2024)
Double track learning can increase creative products in the culinary business sector. A gap has been found to prepare entrepreneurial readiness. High school graduates are a priority to fill industry needs, through double track. RI Presidential Instruction Number 9 of 2020. Overhauling the education system requires harmonization and development of both soft skills and hard skills needed by high school graduates through learning creative entrepreneurial products. The research objective is to analyze the implementation of learning outcomes using the double track program at SMAN 4 Sidoarjo by creating creative entrepreneurial products in the culinary sector. The method used is development research, learning experiments on creative entrepreneurial products, analyzing food product innovation and work readiness of high school students as a provision for work readiness. A descriptive qualitative approach was implemented in 4 classes that took part in double track learning. Data collection techniques: performance observation, interviews and documentation, followed up by Focus Group Discussion (FGD) activities to answer unanswered problems objectively. This research uses triangulation analysis to determine the validity of the data and research findings. The results of the recommendations can be continued with a creative entrepreneurial product learning design designed to integrate basic competencies that are created in line with the teaching and learning process. Alignment of the development of material needed by students. Research findings resulting from exploration of the implementation of creative entrepreneurial product learning are recommended for improving double track learning in accordance with basic competency guidelines for mastering creative entrepreneurial product learning.